(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
The article investigates the influence of different feeding methods on the growth and productivity of the Bukhara-8 variety of cotton under drip irrigation, conducted in the conditions of alluvial soils within the long-irrigated meadows of the Bukhara region. The nutrient composition of the normally fed variant is detailed as follows: N-200; P2O5-150; K2O-100.